2018
DOI: 10.1177/2515690x18804779
|View full text |Cite
|
Sign up to set email alerts
|

Variability of Burnout and Stress Measures in Pediatric Residents: An Exploratory Single-Center Study From the Pediatric Resident Burnout–Resilience Study Consortium

Abstract: Residency is a high-risk period for physician burnout. We aimed to determine the short-term stability of factors associated with burnout, application of these data to previous conceptual models, and the relationship of these factors over 3 months. Physician wellness questionnaire results were analyzed at 2 time points 3 months apart. Associations among variables within and across time points were analyzed. Logistic regression was used to predict burnout and compassionate care. A total of 74% of residents compl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
12
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 50 publications
1
12
0
1
Order By: Relevance
“…With our data, we confirm crosssectional studies reporting several protective factors for burnout, such as that more mindfulness is associated with a lower risk of burnout. 30,31,33,72,[79][80][81][82] Also confirmed in our data are earlier findings that self-compassion, CCC, and empathy are associated with a lower burnout risk. 30,38,76,82,83 Controlled trials are needed to evaluate the impact on burnout of programs that improve mindfulness, self-compassion, and CCC.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…With our data, we confirm crosssectional studies reporting several protective factors for burnout, such as that more mindfulness is associated with a lower risk of burnout. 30,31,33,72,[79][80][81][82] Also confirmed in our data are earlier findings that self-compassion, CCC, and empathy are associated with a lower burnout risk. 30,38,76,82,83 Controlled trials are needed to evaluate the impact on burnout of programs that improve mindfulness, self-compassion, and CCC.…”
Section: Discussionsupporting
confidence: 89%
“…Like others, we found that sleepiness, fatigue, stress, worklife conflicts, and dissatisfaction were associated with an increased risk of burnout. 4,26,34,[69][70][71][72][73] Interventions addressing these factors may be worthwhile to test to reduce burnout. 74 On the other hand, we did not confirm some reported risk factors for burnout, for example, sex and debt.…”
Section: Discussionmentioning
confidence: 99%
“…Specific examples linked to increased burnout include emotional exhaustion, anxiety during medical school, neuroticism personality trait, increased use of electronic health record and occupational stress [5,[18][19][20]. However, protective factors such as personal resilience, mindfulness, self-compassion, reported levels of empathy and extraverted personalities have been associated with decreased burnout [5,10,13,21,22].…”
Section: Discussionmentioning
confidence: 99%
“…5 Work hour restrictions, self-care workshops, and a meditation intervention improve burnout. 6 Resilience 7,8 and mindfulness 9 are associated with decreased burnout. However, burnout is not a phenomenon that occurs in isolation.…”
mentioning
confidence: 99%